Menguak Entrepreneurship Perspektif Qur’an: Karakter Tokoh Pengusaha Muslim Mesir - Mais, Rimi Gusliana (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this analysis is to examine the successful entrepreneurial behavior of Ir. Sholah Al Athiyah is a businessman residing in Egypt. This study aims to fill a void in Muslim entrepreneurship literature and reveal new insights that have yet to be explored by other researchers. As the definition of entrepreneurship remains a topic of discussion, this study turns to the Al-Qur'an as a source of deeper understanding. By examining the teachings of the Al-Qur’an, this article explores Ir. Sholah Al Athiyah's attitude towards Islamic entrepreneurship. With the development of large corporations, it is essential to conduct research that references the Al-Quran and Islamic figures. This study employs a library research method and scientific articles as data sources. The results highlight several fundamental verses that relate to the attitudes of business actors when running a business. Ultimately, the concept of Islamic entrepreneurship aligns with Ir. Sholah Al Athiyah's values are that he always adheres to the teachings of the Al-Qur’an and considers Allah SWT the main investor